Peran mindfulness dalam mengurangi gejala depresi bagi remaja - Salsabila, Rakna Salsabila (Maliki Interdisciplinary Journal, 2025)
Depression is often a topic of conversation, especially among teenagers. Many teenagers today suffer from various mental health disorders. This can be caused by various factors, both internal factors of each individual and external factors. Mental health disorders cannot be ignored. Because we know that the adolescent generation is the milestone of the future. The quality of adolescents determines our nation in the future. Therefore, mental health disorders in adolescents must be addressed immediately. Mindfulness can be an effort in reducing symptoms of depression. Mindfulness trains individuals to regulate and stay in control of choices, behaviors, and feelings. So that with mindfulness can leave the negative emotions that exist in each individual.